The Effects of Blue Light and Supplemental Far-Red on an In Vitro Multiple Harvest System for the Production of Cannabis sativa - Molly McKay; James E. Faust; Matthew Taylor; Jeffrey Adelberg (Plants)
Blue and supplemental far-red light were observed to affect in vitro shoot growth with Cannabis sativa (‘BaOx’ and ‘Cherry 1’) in RV750 vessels. A modified “hedging” and fed-batch system for multiple harvests using Oasis® foam and 120 mL DKW medium was used. Fifteen nodal and/or apical tips were planted and placed into PAR light treatments providing various red to blue ratios (polychromatic white 9:1 RB and dichromatic 2–15: 1 RB, with and without 5% far-red light). Treatments had similar light intensities (190–240 µmol · m−2 · s−1 PPFD) for a 16 h photoperiod. Shoot tips were harvested in vitro on five successive two-week cycles, with 15 mL of DKW media supplemented to each vessel following harvest. Shoot numbers, length, and fresh and dry mass were recorded at each cycle harvest. Five randomly selected shoot tips per vessel were rooted ex vitro on greenhouse mist bench for 16 days. Over multiple cycles, 5% far-red increased shoot numbers and length in both genotypes tested, regardless of polychromatic or dichromatic source. Shoots harvested per vessel increased from 15 to 28 in three cycles (6 weeks), but increased from 15 to 18 without far-red treatment. Shoot length in far-red-treated plants increased from 19 to 25 mm during cycles 1–3. Plants without far-red treatment were approximately 15 mm during the first three cycles. By cycle 5, both far-red- and non-far-red-treated plants decreased to 10 mm. Dry mass was greatest in cycle 1 for both genotypes (‘Cherry 1’ was 6 mg and ‘BaOx’ was 7 mg) under the highest amount of blue light, but 2 mg under the lowest amount of blue light. Dry mass decreased by 50% in cycle 3, to 4 mg, where it remained for the duration of the experiment. Sixty eight percent of shoots rooted ex vitro on the mist bench, regardless of any prior in vitro treatment.